MANAGEMENT OF VARICELLA ZOSTER IN ADULT PATIENT (Case report) - Maharani Laillyza Apriasari; Selviana Rizky Pramitha (FKG Unlam, 2019)
Background: Varicella zoster is a self-limiting disease arising from acute primary infection in skin and mucosa. This disease frequently occurs in children. Its emergence in adult patient may aggravate the symptoms. Purpose: To elaborate the management of Varicella zoster in adult patient. Case: 40 years old female was presented with lips and mouth ulcers for the past two days. Prior to ulceration, itchy watery wheals were manifested on her face and continuously spread to the whole body. Patient confirmed that she experienced this condition for the first time and initially given Acyclovir 400 mg and Paracetamol 500 mg from Community Health Centre healthcare provider. After regularly consuming prescribed drugs for four days, fever and ulcerations had not been subsided. Case management: Intraoral examination displayed one to two milimetre painful multiple ulcers, yellow in color, with regular margin surrounded by erythema on left upper lip, lower lip, and posterior palatum mucosa. Patient was subsequently prescribed with Acyclovir tablet 800 mg four times a day, Ibuprofen tablet 400 mg three times a day, multivitamin B complex and C caplet once a day and aloevera-containing mouthwash to be applied thrice daily. Conclusion: Varicella zoster in patients older than thirteen should be given antiviral therapy to prevent future complications.